2017
DOI: 10.1371/journal.pcbi.1005792
|View full text |Cite
|
Sign up to set email alerts
|

The structured ‘low temperature’ phase of the retinal population code

Abstract: Recent advances in experimental techniques have allowed the simultaneous recordings of populations of hundreds of neurons, fostering a debate about the nature of the collective structure of population neural activity. Much of this debate has focused on the empirical findings of a phase transition in the parameter space of maximum entropy models describing the measured neural probability distributions, interpreting this phase transition to indicate a critical tuning of the neural code. Here, we instead focus on… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 67 publications
2
9
0
Order By: Relevance
“…The figures presented in this section are based on the temporal bin size ∆t = 50 ms, thus striking a good balance between capturing correlations among neurons and providing enough data for analysis. This value of ∆t is slightly larger than the conventional 20 ms window used for retinal neurons [10,21,23,58], reflecting the sparsity of activity patterns in the temporal cortex [59]. We repeated our analysis for both smaller (∆t = 20 ms) and larger (∆t = 100 ms) time bins, and confirmed that our conclusions also hold on these time scales.…”
Section: Resultssupporting
confidence: 67%
“…The figures presented in this section are based on the temporal bin size ∆t = 50 ms, thus striking a good balance between capturing correlations among neurons and providing enough data for analysis. This value of ∆t is slightly larger than the conventional 20 ms window used for retinal neurons [10,21,23,58], reflecting the sparsity of activity patterns in the temporal cortex [59]. We repeated our analysis for both smaller (∆t = 20 ms) and larger (∆t = 100 ms) time bins, and confirmed that our conclusions also hold on these time scales.…”
Section: Resultssupporting
confidence: 67%
“…In previous work, we found that the strength of pairwise correlations between retinal ganglion cells was not precisely tuned to produce clusters, but was instead well within the range required [15]. The robustness of the clustered state suggests that neural populations elsewhere in the brain may also have sufficient correlation to be organized into clusters.…”
mentioning
confidence: 81%
“…In fact, depending on the characteristics of neural noise, redundant population codes can be optimal for encoding information [9,10]. In this context, an appealing principle for population codes is that correlations among neurons organize neural activity patterns into a discrete set of clusters, which can each be viewed as an error-robust population codeword [11][12][13][14][15].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…To this end, we stimulated the retina with different natural movie clips (one of leaves blowing in the breeze, another of water in a river), again finding nearly identical heat capacities (Figure 3B). We also tested artificial stimulus ensembles, like flickering checkboards or spatially uniform flicker (Tkačik et al, 2014;Ioffe and Berry, 2017), and found that in all cases, the neural population was in a low temperature state poised close to criticality. These results have been reproduced in other labs, as well (Yu et al, 2013;Mora et al, 2015;Huang and Toyoizumi, 2016;Hahn et al, 2017).…”
Section: Robustness Of the Glassy Statementioning
confidence: 99%